Madrasah Hadits dan Sejarah Perkembangannya: Menghubungkan Tradisi dengan Inovasi dalam Studi Islam Kontemporer - Yudi Imana; Engkos Kosasih; Syaeful Rokim (Yayasan Cendekia Gagayunan Indonesia, 2025)
This article explores the crucial role of Madrasah Hadis in the development of Islamic studies as an institution that successfully integrates traditional values with innovative elements. As the second source of Islamic law after the Qur'an, Hadith plays a central role in guiding Muslims both spiritually and practically. Madrasah Hadis functions not only as a center for the education and study of Hadith but also as an intellectual gathering place where scholars and students exchange ideas on the application of Hadith in everyday life. The historical development of Madrasah Hadis reflects the transition from oral tradition to the systematic collection and codification of Hadith, with significant contributions from prominent scholars such as Imam Bukhari and Imam Muslim. In the digital age, these madrasahs continue to evolve by utilizing technology to expand access to Hadith education, ensuring that Islamic teachings remain relevant within the modern social and cultural dynamics. This article highlights the importance of Madrasah Hadis as a bridge between the scholarly heritage of Islam and the challenges of the present era.